A Study of Google Form as an Assessment Tool in English Subject at SMAN 2 Solok - Johan Pratama; Nora Fudhla (Universitas Negeri Padang, 2022)
This article deals with the use of google form as an assessment tool in english subject at SMAN 2 SOLOK. The research undertaken aimed to know how do teachers and students perceive about google form as an assessemnt tool in english subject. This study was descriptive qualitatie research. The participants of the research were 70 students as representative of Natural science class in XI grade at SMAN 2 SOLOK. The instrumentation of this research were collected from interview with teachers and questionnaire for students. As for the points to the instrumentations there were aspect of validity, reliability, efficiency, economical, direction, and interest. The findings of this research shows that both teachers and students have good perception about the use of google form as assessment tool in english.